2021
DOI: 10.1111/1758-2229.12956
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the white truffle Tuber magnatum in a limited geographic area of Central‐Southern Italy

Abstract: Summary Molise region (Central‐Southern Italy) is one of the Italian richest areas of truffles and contributes significantly to the national production of the precious Tuber magnatum. Nevertheless, Molise truffle has received little scientific attention. Accordingly, in the present study, two T. magnatum populations collected in two different sites of Molise region were characterised from a morphological, genetic and microbiological point of view. A considerable variability between and within the two analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…These taxa have been suggested to include phosphate‐releasing and iron‐releasing mycorrhiza‐helper bacteria (Pointing et al ., 2009). Moreover, the former class comprises mostly oligotrophic bacteria with potentially relevant functions for host fungi, such as denitrification and nitrogen fixation (Barbieri et al ., 2010; Gohar et al ., 2020; Monaco et al ., 2021). Nevertheless, it remains unclear whether the observed host effect on the community structure of MIB stems from host–microbe co‐evolution or intrinsic (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These taxa have been suggested to include phosphate‐releasing and iron‐releasing mycorrhiza‐helper bacteria (Pointing et al ., 2009). Moreover, the former class comprises mostly oligotrophic bacteria with potentially relevant functions for host fungi, such as denitrification and nitrogen fixation (Barbieri et al ., 2010; Gohar et al ., 2020; Monaco et al ., 2021). Nevertheless, it remains unclear whether the observed host effect on the community structure of MIB stems from host–microbe co‐evolution or intrinsic (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…bisporus when grown in commercial substrates could reshape its original bacterial community (Carrasco et al ., 2020) which later may contribute to the core MIB community (Vieira and Pecchia, 2021). Microbial communities associated with other eukaryotes vary across geographic locations (Arnold and Lutzoni, 2007; Aslani et al ., 2020; Lin et al ., 2020; Monaco et al ., 2021), and such variations have been attributed to the local climatic conditions, the soil microbial community, as well as microbial nutrition source (Van Geel et al ., 2018; Dong and Gupta, 2019). Other studies have found that the community structure of the free‐living microbiome is distinct from the host‐associated microbiome in which ecosystem type was a secondary determinant of community structure (Thompson et al ., 2017; Bahram et al ., 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, inoculation with Tuber spp. changed the nitrogen content in ectomycorrhizosphere ( Li et al, 2018 ; Yang et al, 2019 ), possibly due to the enrichment of nitrogen cycle-related bacteria in the truffle ascocarps ( Barbieri et al, 2010 ; Vahdatzadeh et al, 2015 ; Monaco et al, 2021 ), ectomycorrhizae, and mycorrhizosphere ( Beatrice et al, 2012 ; Le-Roux et al, 2016 ). Denitrification is a key nitrogen-transforming process which results in nitrogen loss in soil ( Bárta et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%